MecC MRSA in Israel—genomic analysis, prevalence and global perspective. Issue 4 (27th August 2022) - Baum, Moti; Anuka, Einav; Treygerman, Orit; Prajgrod, George; Valinsky, Lea; Rokney, Assaf
Abstract: Background: MRSA is a major global healthcare problem. In 2011, a new mec variant designated mecC was described, presenting partial identity at the DNA level, thus undetectable by routine mecA PCR. Objectives: Until now, no reliable information regarding mecC MRSA prevalence was available in Israel. In this study, to the best of our knowledge, we describe the first case of mecC MRSA in Israel, with focus on genomic analysis and global context. Methods: The mecC MRSA isolate was analysed by WGS with focus on phylogeny, global contextualization, virulence and resistance genes. The strain was characterized by antibiotic susceptibility testing, spa typing and presence of mecA/C and pvl genes. Results: An MRSA strain (SA10610), isolated from a urine sample of an 83-year old patient, was found negative for the mecA and pvl genes. The MLST and spa type were ST130 and t1736, respectively. SA10610 presented resistance to oxacillin, penicillin and cefoxitin, and susceptibility to all non-β-lactam agents tested. Phylogenetic comparison with a global dataset of 586 mecC MRSA genomes revealed substantial genomic divergence. The nearest genomic relatives were human and animal isolates from Denmark. A screen of 12 761 S. aureus isolates collected during 2011–18 in Israel indicated this is the only mecC -positive strain. Conclusions: A high degree of genetic variability was found between the SA10610 strain and previously sequenced mecC MRSA isolated worldwide. The genomic and phylogenetic analysis suggest that mecC MRSA isolates have evolved independently rather than from a common ancestor.